DIGITASI BAHAN PUSTAKA NON-BUKU LEKSI PERPUSTAKAAN REKSO PUSTOKO ANGKUNEGARAN SURAKARTA, JAWA TENGAH - Priyomarsono, Naniek Widayati; Yuono, Doddy; Harsiti, Harsiti (Jurnal Bakti Masyarakat Indonesia, 2020)
Pura Mangkunegaran in Surakarta, holds many unique cultures, classics, and amazing architecture. In addition it has a library that holds 13,871 book titles, more than 15,000 titles of written documents / ancient manuscripts, and 40,000 pictures / photos with rare information worth of historical relics of the nation. The problem that arises is the financial factor so that it cannot use professional staff both in quantity and quality. Storage of documents has not been organized and is well maintained, so that the search for information is very difficult and physically the document becomes faded, the paper is getting worn, damaged, so that its preservation is not maintained. On the other hand, the existence of Puro Mangkunegaran as a tourist location is open to the public, and every day the Rekso Pustoko Library is visited by students, students, teachers, and researchers looking for information. The reason is encouraging Tarumanagara University through its Research and Community Engagement Institute (LPPM), to do the Digitizing of Non-Book Library Material Collection of Rekso Pustoko Library. The aim of digitizing is to preserve the libraries of royal events with valuable information, efficient use of space, practical, easy management, optimizing information utilization through on-line, widely publicized, facilitating information dissemination, and promoting Mangkunegaran Temple. The method uses observation techniques, survey techniques, literature studies, interviews, and digitization to shoot non-book documents (pictures / photos), using a camera. The results of digitization activities were 2000 pictures / portraits in digital form. Expected output: the realization of digitization helps manage digital library materials, facilitates retrieval, optimizes information utilization, facilitates dissemination, preserves scarce information, and promotes Mangkunegaran Temple. The results are published in posters, and proceedings ABSTRAK: Pura Mangkunegaran di Surakarta, menyimpan banyak budaya unik, klasik, dan karya arsitektur yang mengagumkan. Selain itu mempunyai perpustakaan menyimpan 13.871 judul buku, lebih dari 15.000 judul dokumen tertulis/naskah kuno, dan 40.000 gambar/foto bernilai informasi langka sejarah peninggalan bangsa. Masalah yang timbul adalah faktor finansial sehingga belum bisa menggunakan tenaga professional baik kuantitas maupun kualitas. Penyimpanan dokumen belum tertata dan terawat baik, sehingga pencarian informasi sangat sulit dan secara fisik dokumen menjadi pudar, kertasnya mulai usang, rusak, sehingga kelestariannya belum terjaga. Di lain fihak, eksistensi Puro Mangkunegaran sebagai lokasi wisata dibuka untuk umum, setiap harinya Perpustakaan Rekso Pustoko banyak dikunjungi para siswa, mahasiswa, pengajar, dan peneliti mencari informasi. Alasan tersebut mendorong Universitas Tarumanagara melalui Direktorat Penelitian dan Pengabdian Kepada Masyarakat (DPPM), melakukan Digitasi Bahan Pustaka Non-Buku Koleksi Perpustakaan Rekso Pustoko. Tujuan digitasi untuk melestarikan bahan pustaka peristiwa kerajaan bernilai informasi langka, efisiensi penggunaan ruangan, praktis, memudahkan pengelolaan, mengoptimalkan pemanfaatan informasi melalui on-line, terpublikasi secara luas, memudahkan desiminasi informasi, dan mempromosikan Pura Mangkunegaran. Metode menggunakan teknik observasi, teknik survei, studi literatur, wawancara, dan digitasi melakukan pemotretan dokumen non buku (gambar/foto), menggunakan kamera. Hasil kegiatan digitasi sebanyak 2000 gambar/potret dalam bentuk digital. Luaran yang diharapkan: terealisasinya digitasi membantu pengelolaan bahan pustaka digital, memudahkan pencarian kembali, mengoptimalkan pemanfaatan informasi, memudahkan desiminasi, melestarikan informasi langka, dan mempromosikan Pura Mangkunegaran. Hasilnya dipublikasikan dalam poster, dan prosiding.